Selective Vascular Endothelial Growth Factor Receptor Inhibitors Provide Limited Benefits for Metastatic Colorectal Cancer: A Meta-Analysis - Fan, Qin; Lv, Wenhao; Xu, Yuexin; Dong, Yuan; Xiang, Zhiqiang; Wang, Junjie (Current pharmaceutical design, 2020)
Metastatic colorectal cancer (mCRC) is one of the most common and deadly cancers worldwide. For most patients diagnosed with mCRC and managed with 5-fluorouracil (5-FU)/leucovorin plus oxaliplatin (FOLFOX), the median survival time is still less than 2 years. Small molecule selective vascular endothelial growth factor receptor (VEGFR) inhibitors have been demonstrated to have strong anti-tumour activity in various cancer models. To demonstrate the efficacy and safety of selective VEGFR inhibitors in the management of mCRC. A comprehensive search in PubMed, EMBASE, Web of Science, Ovid MEDLINE, Google Scholar, Springer and Cochrane Central databases was performed for randomized controlled trials (RCTs) focusing on the effect of selective VEGFR inhibitors on mCRC. The primary outcome measures were progression-free survival (PFS) rates, overall survival (OS) rates, complete response (CR), partial response (PR), stable disease (SD), progressive disease (PD), objective response rates (ORRs), disease control rates (DCRs) and adverse effect (AE) rates. The dates of the included studies ranged from the inception of the database to January 15, 2020. Twenty-two RCTs were included. A total of 9362 patients met the inclusion criteria. Compared with placebo, selective VEGFR inhibitors significantly increased the PFS rate, SD, PR and DCR, reduced PD, caused more treatment-emergent adverse events (TEAEs), hypertension, hand-foot skin reaction, diarrhoea, fatigue, and thrombocytopaenia and increased aspartate aminotransferase(AST) concentration. There was no significant difference between selective VEGFR inhibitors and placebo regarding OS rate, CR, ORR, proteinuria, hyperbilirubinaemia or alkaline phosphatase(ALP) concentration. Additionally, compared with FOLFOX4+placebo, FOLFOX4+ selective VEGFR inhibitors, clearly reduced PD, and caused more 3-4 AEs, serious AEs, hypertension, hand-foot syndrome, diarrhoea, nausea, vomiting, decreased appetite, dehydration, fatigue, dizziness, neutropaenia and thrombocytopaenia. For PFS rate, OS rate, CR, PR, SD, ORR, abdominal pain, peripheral sensory neuropathy, asthaenia, anaemia and hypokalaemia rates, there was no significant difference between FOLFOX4+ selective VEGFR inhibitors and FOLFOX4+placebo. However, compared with FOLFOX4+bevacizumab, FOLFOX4+selective VEGFR inhibitors, led to increased hypertension, neutropaenia, fatigue, thrombocytopaenia and asthaenia. There is no clear difference between FOLFOX4+selective VEGFR inhibitors and FOLFOX4+ bevacizumab with regard to PFS rate, OS rate, CR, PR, SD, PD, ORR, diarrhoea, nausea, vomiting, peripheral neuropathy and abdominal pain rates. Selective VEGFR inhibitors+cetuximab increased PFS and PR and reduced PD compared to cetuximab, but there was no statistical difference between the two groups for OS and SD. Compared with placebo or cetuximab, selective VEGFR inhibitors alone or combined with cetuximab seemed to be more efficacious for mCRC respectively; however, the effects were not better than FOLFOX4 alone or when combined with bevacizumab for mCRC. Additionally, selective VEGFR inhibitors were not as safe as placebo or FOLFOX4 alone or in combination with bevacizumab in mCRC.